Comprehensive analysis of the expression of N6-methyladenosine RNA methylation regulators in pulmonary artery hypertension - Zheng, Hao; Hua, Jing; Li, Hongpeng; He, Wenjuan; Chen, Xiangyu; Ji, Yingqun; Li, Qiang (Frontiers in Genetics, 2022)
Background: Pulmonary arterial hypertension (PAH) is a progressive disease characterized by pulmonary vascular remodeling. The development of PAH involves N6-methyladenosine (m6A) modification. However, the functional role of m6A regulators in PAH and the underlying regulatory mechanisms remain unknown so far. Methods: Microarray data (GSE149713) for monocrotaline induced PAH (MCT-PAH) rat models were downloaded and screened for differentially expressed genes (DEGs) and m6A regulators. Next, we screened for differentially expressed m6A regulators in endothelial cells (ECs), smooth muscle cells (SMCs), fibroblasts, interstitial macrophages, NK cells, B cells, T cells, regulatory T cells (Tregs) using scRNA sequencing data. The target DEGs of m6A regulators in ECs, SMCs, fibroblasts, and Tregs were functionally annotated using the Gene Ontology (GO) functional analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis.In addition, the cellular interaction analysis was performed to reveal the receptor–ligand pairs regulated by m6A regulators. Pseudo-time trajectory analyses were performed and a ceRNA network of lncRNAs-miRNAs-mRNAs was constructed in SMCs. Furthermore, the RNA transcriptome sequencing data for the SMCs isolated from idiopathic PAH(IPAH)patients (GSE144274) were validated for differentially expressed m6A regulators. Moreover, the HNRNPA2B1 levels in the lung samples from PAH patients and MCT-PAH were determined using immunohistochemistry. Results: The m6A regulators were observed to be dysregulated in PAH. HNRNPA2B1expression level was increased in the PASMCs of scRNAs and IPAH patients. The target DEGs of HNRNPA2B1 were enriched in the regulation of muscle cell differentiation and vasculature development in PASMCs. The HNRNPA2B1 expression levels determined were consistent with the proliferation-related and collagen synthesis-related gene COL4A1. Moreover, the predicted transcription factors (TFs) foxd2/3 and NFκB could be involved in the regulation of HNRNPA2B1. HNRNPA2B1 might be regulating SMCs proliferation and phenotypic transition via rno-miR-330–3p/TGFβR3 and rno-miR-125a-3p/slc39a1. In addition, HNRNPA2B1 was observed to be highly expressed in the lung samples from MCT-PAH rat models and patients with PAH. Conclusion: In summary, the present study identified certain key functional m6A regulators that are involved in pulmonary vascular remodeling. The investigation of m6A patterns might be promising and provide biomarkers for diagnosis and treatment of PAH in the future.